PHYSICAL ATTRIBUTES OF A LATOSOLO AFTER THE USE OF DOSES WITH POULTRY LITTER ADDED MINERAL FERTILIZATION (Colloquium Agrariae. ISSN: 1809-8215, 2019)
Wastes from agroindustrial activity have been commonly used in agriculture, isolated or even associated with mineral fertilizers, and can alter the physical properties of the soil. This study aimed to evaluate the effects of the use of mineral and combined fertilizers with poultry litter (CF) on the physical attributes of a Cerrado Latosol. The experiment was conducted in a randomized block design with four treatments and five replicates. The treatments were as follows: AM - Mineral fertilization with 220 kg of 00-32-00 + 150 kg of KCl ha-1; AM + 2 Mg ha-1 CF; AM + 4 Mg CF; AM +6 Mg CF. After the fourth year of chicken litter use associated with mineral fertilizers, samples were collected to determine soil physical attributes at depths of 0 - 0.05 m, 0.05 - 0.10 m and 0.10 - 0.20 m. The association of chicken litter, with mineral fertilization, at the highest doses tends to increase the total pore volume of 0.45 m3 m-3 in the AM treatment, reaching 0.53 m3 m-3 in the AM + 4 Mg ha-1 CF. The microporosity obtained a similar behavior to VTP, going out 0.32 m3 m-3 in AM reaching 0.40 m3 m-3 in AM + 4 Mg ha-1 CF. However the weighted average diameter of aggregates were reduced from 2.95 mm in AM to 2.43 mm in AM + 6 Mg ha-1 CF. The percentage of macroaggregates was reduced with the addition of higher doses the poultry litter to mineral fertilizer.